Recaudaciones para empresas administradoras de fondos basadas en indicadores de cobranzas y territorios de ventas - Villamar Monteros, Sofia Margarita (2022)
This research work is entitled "COLLECTIONS FOR FUND MANAGING COMPANIES BASED ON COLLECTION INDICATORS AND SALES TERRITORIES". The problem that we are trying to solve is the correct allocation of a sales territory for the Fund Administrators that allows generating higher collection rates for them and the timely identification of their clients' records, with tools and a design that allow choose the right sales territory so that sales are effective that can last over time and that affects the productivity of the commercial area. The context is based on the consideration of the development of a methodology that allows determining the appropriate sales territory for Fund Administrators. The main contribution that the implementation of the proposal will have been that it will allow management in a timely manner which are the stages for the selection of a sales territory according to the business line and to be able to obtain the results that the organizations expect, which is an increase. in the collections. This research has a quantitative and qualitative approach that will allow us to know the lived experiences of the people we are going to interview.......